Co-Injection of Sulfotyrosine Facilitates Retinal Uptake of Hyaluronic Acid Nanospheres Following Intravitreal Injection - Aiden Eblimit; Mustafa S. Makia; Daniel Strayve; Ryan Crane; Shannon M. Conley; Tirthankar Sinha; Ghanashyam Acharya; Muayyad R. Al-Ubaidi; Muna I. Naash (MDPI AG, 2021)
Gene and drug delivery to the retina is a critical therapeutic goal. While the majority of inherited forms of retinal degeneration affect the outer retina, specifically the photoreceptors and retinal pigment epithelium, effective targeted delivery to this region requires invasive subretinal delivery. Our goal in this work was to evaluate two innovative approaches for increasing both the persistence of delivered nanospheres and their penetration into the outer retina while using the much less invasive intravitreal delivery method. We formulated novel hyaluronic acid nanospheres (HA-NS, 250 nm and 500 nm in diameter) conjugated to fluorescent reporters and delivered them intravitreally to the adult Balb/C mouse retina. They exhibited persistence in the vitreous and along the inner limiting membrane (ILM) for up to 30 days (longest timepoint examined) but little retinal penetration. We thus evaluated the ability of the small molecule, sulfotyrosine, to disrupt the ILM, and found that 3.2 µg/µL sulfotyrosine led to significant improvement in delivery to the outer retina following intravitreal injections without causing retinal inflammation, degeneration, or loss of function. Co-delivery of sulfotyrosine and HA-NS led to robust improvements in penetration of HA-NS into the retina and accumulation along the interface between the photoreceptors and the retinal pigment epithelium. These exciting findings suggest that sulfotyrosine and HA-NS may be an effective strategy for outer retinal targeting after intravitreal injection.